Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species - Delvare, Gérard; Heimpel, George E.; Baur, Hannes; Chadee, Dave D.; Martinez, Raymond; Knutie, Sarah A. (Zootaxa, 2017)
In this paper, we describe and illustrate a new species of parasitoid wasp as Brachymeria philornisae Delvare, sp. nov. The new species was reared from Philornis trinitensis Dodge & Aitken (Diptera: Muscidae) puparia that were found in the nests of the bird species Mimus gilvus (Vieillot) (Mimidae) and Tiaris bicolor (L.) (Thraupidae) in Tobago. The new species is of particular interest as it may be considered a potential biological control agent in locations where Philornis species are invasive, such as the Galapagos Islands. Closely related Brachymeria species had taxonomically ambiguous relationship in the past and are compared and reviewed. The species have been classified in the subgenus Pseudobrachymeria, but are here treated within the newly defined subconica species-group of Brachymeria as part of a sibling species complex designated as the subrugosa complex. Species assigned to the subconica species-group are listed and five, one unnamed, are assigned to the subrugosa complex and their females keyed. Species are separated by qualitative characters and morphometry using distance measurements. Trigonura annulipes Costa Lima is renamed as Brachymeria costalimai Delvare nom. nov. because of secondary homonymy.